Analysis of Factors Related to The Utilization of Health Services at UPT Puskesmas Tampang Tumbang Anjir - Ira Mingchilina; Syamsul Arifin; Muhammad Abdan Shadiqi; Eko Suhartono; Bahrul Ilmi (Jurnal Berkala Kesehatan, 2023)
Data from the Ministry of Health show that patient visits to health services in 2020 have decreased by 83.6 percent. This study aims to determine the relationship between the perception of pain, security of ownership, availability of health facilities and utilization of health services at UPT Puskesmas Tampang Tumbang Anjir. Design used with cross sectional method. The population is patients who visited in May 2023 with a total sample of 67 respondents. How to take samples with purposive sampling. Data analysis was descriptive and statistical, namely chi square and multiple logistic regression. The results of the analysis of variables related to the use of health services are perception of illness (p = 0.004 <a 0.05), ownership of health insurance (p = 0.005 <a 0.05) and availability of health facilities (p = 0.000 <a 0.05). The dominant factor is the availability of health facilities because the value of Exp (B) is 8, 262. The conclusion in this study is the variables related to perception of illness, ownership of health insurance and availability of health facilities while the dominant factor is the availability of health facilities.